Selective Carbon Dioxide Hydrogenation to Olefin-Rich Hydrocarbons by Cu/FeOx Nanoarchitectures Under Atmospheric Pressure - Muhammad I. Qadir; Naděžda Žilková; Libor Kvítek; Stefan Vajda (Nanomaterials)
The conversion of carbon dioxide into fuels and fine chemicals is a highly desirable route for mitigating flue gas emissions. However, achieving selectivity toward olefins remains challenging and typically requires high temperatures and pressures. Herein, we address this challenge using 12 nm copper nanoparticles supported on FeOx micro-rods, which promote the selective hydrogenation of CO2 to light olefins (C2–C4) under atmospheric pressure. This catalyst achieves up to 27% conversion and 52% selectivity toward C2–C4 olefins, along with the production of C2–C4 paraffins, C5+ hydrocarbons (with all C1+ products totalling to up to about 75%), and methane, while suppressing CO formation to just 1% at 340 °C. The enhanced performance of the Cu/FeOx pre-catalyst is attributed to the efficient in situ generation of iron carbides (Fe5C2) in the presence of copper nanoparticles, as confirmed by ex situ XRD analysis. Copper facilitates the reduction of FeOx to form Fe5C2, a crucial intermediate for shifting the reaction equilibrium toward higher hydrocarbons. The hydrogenation of CO2 to higher hydrocarbons proceeds through the reverse water–gas shift reaction coupled with Fischer–Tropsch synthesis.